Coordination between racket and ball: Age effect on information strategy in table tennis service - Chuang, K. L.; Liu, Y. T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Table tennis is a sport of interceptive actions. The coordination between the ball and racket, or timing performance, plays paramount importance in executing the interceptive actions in table tennis. The affordance of the environment reflects the coupling relations between an individual and the environment, which may be considered as an information strategy that is adopted by the individual to guide the skill development. When performing the same interceptive action, table tennis players of different developmental stages may use different information strategies due to their different experience and growth factors. The fast deep flat service is one of the most fundamental yet important table tennis skills that should be mastered in the early stages of training. The purpose of the study was to examine the different information strategies used by children and adult table tennis players when performing the fast deep flat services. Methods: 8 male collegiate table tennis club players (19-22 yrs), and 8 boys (9-10 yrs) from the table tennis team of an elementary school participated in the study. Participants were asked to aim for a 30x30 cm2 target area and performed 20 fast deep flat services. 2 highspeed cameras and the Kwon 3D digitizing system were used to capture the kinematics of the ball and racket. Independent sample ttests were used to compare the service and timing performances of two groups. Pearson product-moment correlations were calculated to examine the various relations of the timing measures for each group. Results: There were no significant differences for the service performances measured in the rate of hit, racket velocity at ball-bat contact, and the maximal forward velocity of the racket between the 2 age groups. However, children had significantly more variability in the performance of movement initiation than adults. In addition, children also showed a significantly higher coefficient of correlation between the racket velocity and the distance to the ball-bat contact at the start of forward acceleration phase. Discussion: It was expected that there would be no difference in the service performance between the 2 groups because both groups of participants had been trained in table tennis for about 2 years. However, the differences of the various timing performance measures between the age groups reflected the different information strategies adopted by different age groups as a result of the difference in their developmental stages. Although children had more variability in the movement initiation, they were able to successfully carry out the service performance with the tight coupling between these movement initiation parameters. Adults, on the other hand, were able to use the information of the ball to control the movement initiation and showed a more stable timing performance than children. Future studies will examine table tennis players of different skill levels in order to explore the relation between timing performance and skill level.